The Human Being in Eschatology according to 1 Thess 5:23 - García Serrano, Andrés (The Biblical Annals, 2022)
In his earliest letter, 1 Thessalonians, Paul addresses the issue of eschatology, leaving us a surprising anthropological description of the human being as “spirit, soul, and body.” Paul uses terms that are familiar to his readers. However, the first term in this threefold division of a human being, “spirit,” is the most emphasised, since the human being is no longer made up exclusively of “body and soul.” In this brief contribution, I will attempt to examine this term, “spirit,” as illuminated by its immediate narrative context and by other Pauline pneumatological texts and by its first reception. In this way, the reader will better understand the Pauline vision of the human being in the eschatology, in his ultimate destiny.